Effect of beet flour on films made from biological macromolecules: Native and modified plantain flour - Gutiérrez Carmona, Tomy José (2016)
Biological macromolecules such as starches of different amylaceous sources have been used in the formulation of edible films. However, there are few studies aimed at evaluating edible and intelligent films with response to pH changes from natural pigments, this despite the importance of these materials. In this context, films from native and modified plantain flour, plasticized with glycerol, with or without the addition of beet flour were developed. The chemical and structural composition of the flours, and its incidence on thickness, water solubility, contact angle, and mechanical and microstructural properties were evaluated, thus as its response to pH changes of the developed films. The observations showed that the incorporation of beet flour allowed to obtain intelligent films front to pH changes alkaline. Likewise, the betalains that were found in beet flour interacted more efficiently with the phosphated plantain flour, limiting well its immediate response to pH changes. In the same way, proteins and sugars of beet flour allowed to obtain more flexible films, due to the hydrogen bond interactions between these constituents and the plantain flours. This latter could justify the decrease of contact angle, and the increase on thickness and solubility of these films.